Pemberdayaan Masyarakat melalui Program â€œKampung InggrisMengajarâ€ di Kampung InggrisKecamatan Pare Kabupaten Kediri - Nurcahyaningtias, Pipit; Askafi, Eka; Baehaki, Imam (Otonomi, 2024)
Actively mastering English has become a necessity. In its development, English has become a lingua franca and is used as a measuring tool in various types of work. Kampung Inggris in the Pare - Kediri has become an English learning center visited by students from various cities in Indonesia. In fact, the potential of Kampung Inggris is not comparable to the empowerment of local residents, most entrepreneurs are dominated by residents from outside Pare. The local residents' poor English language skills prompted the Forum Kampung Bahasa to initiate the "Kampung InggrisMengajar" activity to increase the ability of local communities to speak English in order to support the development of English Village as an English-speaking area. This research aims to explain the management of the Kampung InggrisMengajar program, identify the obstacles faced in implementing the KIM program and the implications of the KIM program. This research uses a qualitative approach with data collection methods using observation, interview and documentation techniques. The research results show that the KIM program helps the community to participate in the promotion of Kampung Inggris with the increasing number of English speakers in English Village which is an attraction for students who come to Kampung Inggris